Toxicidade de aditivos e de formulados de Metarhizium anisopliae s.I. IP46 em adultos de Aedes aegypti e conidiogênese quantitativa na fase saprobiôntica - Borges, Priscilla Rodrigues (2012)
Aedes aegypti is both the dengue and urban yellow fever vector in Brazil. Elimination of this mosquito is a strategy taken for the control of dengue. Entomopathogenic fungi such as Metarhizium anisopliae exhibit ovicidal, larvicidal and adulticidal activity on A. aegypti, being therefore of great interest for the integrated control of such mosquito. Water based, oil based, water/oil/powder based fungal formulations may help such fungi overtake environmental adverse effects as well as magnify their entomopathogenic action. Nevertheless, little is known about the effect of additives on A. aegypti adults. This study reports the effect of additives such as diatomaceous earth and oils (both vegetal and mineral), with or without the presence of M. anisopliae conidia IP 46 on A. aegypti adult mosquitoes, the effect of exposure time on accumulated mortality of such mosquitoes as well as the effects of formulations on conidiogenesis on dead adult mosquitoes killed by infection. Graxol ® vegetable oil was tested in two concentrations (0.25 and 0.05 µl/cm 2 ), as well as Naturol ® mineral oil (0,25 µl/cm 2 ) and KeepDry ® diatomaceous earth (0,6 mg/cm 2 ). Such additives were analyzed both separately and in combination (KeepDry ® + Graxol ® ; KeepDry ® + Naturol ® ). Subsequently, oily formulations or combinations of IP 46 at 3.3 x 10 6 conidia/cm 2 + KeepDry ® + oils (Graxol ® or Naturol ® ) were tested. Additives and formulations were applied inside plastic cups. Ten A. aegypti adults were placed in the cup and kept at 25°C, relative humidity of 75% and 12 hours of photophasis with permanent access to a 10% sugar solution. In order to assess the effect of the time of exposure, mosquitoes were exposed to IP 46 conidia (3.3 x 10 6 conidia/cm 2 ) formulations on diatomaceous earth and mineral oil for 0.016 hours (60s), 12 hours, 48 hours, 72 hours and 120 hours. A non-treated control group was kept at the same conditions. Mortality was daily verified for 15 days. Mosquitoes killed by fungal infection were incubated for 10 days in a humid chamber with relative humidity close to saturation (≥ 98%) and then suspended in Tween 80 ® (0,1%) for conidia quantification in Neubauer chamber. Results showed that the additives exert toxicity on A. aegypti adults as well as effect on mortality (F 6 , 35 = 31,9, P = 0,0001). IP 46 conidia combined to pure KeepDry ® or on oil associations took shorter to kill 50% (TL 50 ) of mosquitoes and the IP 46 + KD + N combination took less time to kill 90% (TL 90 ), namely 7.5 days. There was no relevant difference between time of exposure on accumulated mortality of adults exposed to combined and non-combined IP 46conidia. The growth of mycelia on dead adults started within 2 days of humid chamber incubation. New IP 46 conidia where observed from the 3 rd day on, regardless conidia concentration and combination type to which mosquitoes had previously been exposed to. The effect of the combination on quantitative conidiogenesis on dead mosquitoes was significantly different (F 5,18 = 3.8; P = 0.02), a greater number of conidia on dead mosquitoes being found on mosquitoes who were exposed to the IP 46 + KeepDry ® combination. The IP 46 with KeepDry ® and Naturol ® combination proved to be the most recommended one for the control of A. aegypti adults using a mycoinsecticide.